Treasure Hoards of East Anglia and their Discovery. - Mitchels, Mark (Countryside Books, 2013)
Over the years, the fields of East Anglia have brought forth a staggering wealth of treasure from all periods of history, but especially the Roman, Saxon and Viking eras. This book tells the story of these amazing discoveries and many more, and describes where they can be seen today.